Photovoice as an evaluation tool for student learning on a field trip. Issue 2 (3rd May 2016) - Behrendt, Marc; Machtmes, Krisanna
Abstract: Background: Photovoice is one method that enables an educator to view an experience from a student's perspective. This study examined how teachers might use photovoice during an informal learning experience to understand the students' experiences and experiential gain. Design and methods: Participants in this study consisted of six students, three male and three female, ranging from ninth through twelfth grade at a rural Ohio high school, who attended a field trip to a biological field station for a four-day immersive science experience. Students were provided cameras to photograph what they believed was important, interesting, or significant during an immersive four-day science trip to a biological field station, individualizing their observations in ways meaningful to them, and enabling them to assimilate or accommodate the experiences to their schema. Results: Analysis identified five positive benefits to use photovoice as an evaluation tool: teachers were provided qualitative evidence to evaluate student interaction on the field trip; teachers could evaluate the students' photographs and captions to determine if the field trip met the learning objectives; students were empowered to approach the goals and objectives of the field trip by making the field trip personally relevant; students assimilated and accommodated the new observations and experiences to their own schema; students automatically reflected upon the learning experience as they captioned the photos. Conclusions: Through photovoice, the teachers were enabled to qualitatively assess each student's experience and learning from the field trip by illustrating what the students experienced and thought was significant; providing the teachers a method to evaluate all participating students, including those who are secretive or do not normally contribute to class discussions.